Measuring human capital’s contribution to sustainable economic development - Serikkyzy, A.; Baktymbet, S.S.; Baktymbet, A.S. (BUKETOV BUSINESS REVIEW, 2024)
Object: The object is research of human capital through education, healthcare, professional skills, social compe tencies, and their effect on economic sustainability and development. Methods: The methodological basis of the work is comprised of quantitative methods including regression analy sis and econometric modeling. Findings: The following main results showcase human capital’s significant and multifaceted impact on sustaina ble development parameters: 1) Education and healthcare investments have been revealed to contribute to an increase in productivity and eco nomic growth. 2) Research leads to reduction in poverty and improvement of environmental indicators. 3) Human capital development policy making and implementation as an essential element of achieving sustainable economic development. Conclusions: This section offers recommendations for politicians and government agencies on how to form strat egies for the development of human capital. Results of the study can serve as a basis for the formation of effective strat egies to develop human resources in the context of global economic and social challenges.